Analysis of Mathematical Critical Thinking Ability Junior High School Students on Systems of Linear Equations in Two Variables Material - Fadilla, Jihan; Sari, Fitri Wulan; Auladina, Hafizah; Angraini, Lilis Marina; Bonyah, Ebenezer (International Journal of Contemporary Studies in Education, 2024)
The aim of this research is to understand junior high school students' mathematical critical thinking abilities when facing SPLDV problems. The approach applied is a qualitative approach in the descriptive method. Subjects were selected using a purposive sampling technique and then 3 students were selected from 31 students in class VIII-5 of SMP N 1 Tualang. The test instrument used consists of three questions. Then students' responses were categorized into high, medium and low categories and analyzed these responses using indicators of critical thinking skills in the context of mathematics. Research findings show that students in class VIII-5 at SMP N 1 Tualang have critical mathematical thinking skills and are categorized as sufficient. This can be seen in the answers to test questions which do not cover several aspects of mathematical critical thinking skills. Mathematical critical thinking abilities were measured in three categories, high (9.68%), medium category (70.98%), and low category (19.36%).